A Case Report of a Rare Dyke-Davidoff-Masson Syndrome Case - Akash Shah; Meetkumar Patel; Shubham Darda; Sweta Sanandia (Journal of Integrated Health Sciences)
The neurological disorder known as Dyke-Davidoff-Masson syndrome (DDMS) was initially identified in 1933 as hemispheric atrophy. Clinical signs and symptoms include mental impairment, seizures, facial asymmetry, and contralateral hemiparesis. Asymmetric thickening of the calvarium and expansion of the frontal and ethmoid sinuses are among the neuroimaging findings. We present here a case of 19-year-old male who is known case of epilepsy with complaints of multiple episodes of seizures frequently and on magnetic resonance imaging was diagnosed to have DDMS.